Protective effect of milk against dental demineralization: understanding the mechanisms - Cassiano, Luiza de Paula Silva (2017)
This study aimed to answer the following questions: 1) does whole fluoridated milk protect more against enamel and dentin erosion than fat-free fluoridated milk? 2) does the protective effect of fluoridated milk against erosion follow a dose-response relationship? 3) is the treatment with whole or fat-free fluoridated milk before the first erosive challenge more protective against enamel and dentin erosion? 4) does the fat content of milk change the proteomic profile of the acquired enamel pellicle (AEP)? This study was divided into 2 parts. The first part analyzed in vitro the effect of milk against dental erosion, considering three factors: type of bovine milk (whole/fat-free), presence of different fluoride concentrations (0- 10.0 ppm) and time of application (before/after erosive challenge). Bovine enamel (n=15/group) and root dentin (n=12/group) specimens were submitted to the following treatments: 0.9% NaCl solution (negative control)( after first erosive challenge); whole milk with 0, 2.5, 5.0, 10.0 ppm F; fat-free milk with 0, 2.5, 5.0, 10.0 ppm F; 0.05% NaF solution (positive control) (before or after first erosive challenge). Specimens were submitted to demineralization - remineralization regimes, 4 times/ day, for 5 days. The response variables were enamel and dentin loss, evaluated by profilometry (m). Data were analyzed using KruskalWallis/Dunns test (p<0.05). The presence of fluoride, especially at 10 ppm, was the most important factor in reducing dental erosion. The second part detected changes in protein profile of AEP formed in vivo after rinsing with whole milk, fat-free milk or water. Nine subjects with good oral conditions participated. The AEP was formed in the morning, for 120 min, after prophylaxis with pumice. In sequence, the volunteers rinsed with 10 mL of whole milk, fat-free milk or deionized water for 30 s, following a blind, crossover protocol. After 60 min, the AEP was collected with filter paper soaked in 3% citric acid and processed for analysis by liquid chromatography-electrospray ionization tandem mass spectrometry (LCESI- MS/MS). The obtained MS/MS spectra were searched against human protein database (SWISSPROT). The proteomic data related to protein quantification were analyzed using the PLGS software. A total of 260 proteins were successfully identified in the AEP samples collected in all groups. Forty-nine were common to the 3 groups, while 72, 62 and 49 were specific for groups treated with whole milk, fat-free milk and water, respectively. Some were typical components of the AEP, such as Cystatin-B, Lysozyme C, Histatin-1, Statherin and Lactotransferrin. Other proteins are not commonly described as part of the AEP but could act in the defense of the organism against pathogens. Distinct proteomic profiles were found in the AEP after rinsing with whole or fat-free milk, which could have an impact in bacterial adhesion and tooth dissolution. The use of fat-free milk could favorably modulate the adhesion of bacteria in the AEP and the biofilm formation in comparison to whole milk.